Production of antimicrobial paper with natamycin and methylcellulose and evaluation of its printability - URAL, ELİF (My University, 2021)
Food preservation has become one of the important research topics due to developing technology and decreasing resources. One of the methods used to increase the shelf life of food is to make antimicrobial packaging. A package should both promote the product well and protect it. For this reason, the production of printable and antimicrobial packaging paper was investigated within the scope of this study. In this study, methyl cellulose biopolymer containing natamycin in different amounts (0;2,5;5;7.5;10) to produce antimicrobial paper was successfully coated on office paper in a laboratory paper coating device and its antimicrobial properties were measured by disc diffusion method. The gloss and color values of the obtained papers were determined and offset test prints were made with IGT C1. Color and gloss properties of printed papers were measured. As a result, an effective antimicrobial paper was produced with natamycin. The antimicrobial properties of the produced papers increased due to the increased amount of natamycin. In addition, it has been found that the produced papers are suitable for offset printing.
Keywords: natamycin; biopolymer; paper coating; antimicrobial; printing